COMPARATIVE ANALYSIS OF IMBT AND AITAB HIRE-PURCHASE ISLAMIC FINANCING IN THE FRAMEWORK OF MAQASID AL-SHARIAH - Mubarok, Wafiq; Rifqun Nisa; Chetrine Alya Rinaima (Maliyah : Jurnal Hukum Bisnis Islam, 2026)
This study examines the comparative framework of Ijarah Muntahiyah bi al-Tamlik (IMBT) as practised in Indonesia and Al-Ijarah Thumma al-Bayʿ (AITAB) as implemented in Malaysia, focusing on their doctrinal foundations, methodological reasoning, and realisation of Maqāṣid al-Sharīʿah. Using a doctrinal–comparative approach supported by textual analysis of fatwas and institutional regulations, the research identifies that the divergence between DSN-MUI’s IMBT and SAC-BNM’s AITAB reflects two complementary orientations of Islamic jurisprudence. DSN-MUI emphasises a normative–formalist logic, grounded in sadd al-dharāʾiʿ to preserve contract integrity and prevent taʿalluq, while SAC-BNM adopts a functional–pragmatic stance based on istiṣlāḥ and taḥqīq al-manāṭ to promote market efficiency and regulatory certainty. Despite structural differences, both models fulfil the higher objectives of Shariah—ḥifẓ al-māl, ʿadl, amānah, and maṣlaḥah ʿāmmah. The findings suggest that such diversity strengthens cross-border Islamic finance integration through mutual recognition of core Shariah principles and flexible adaptation in operational practices. This complementary plurality confirms that Islamic law remains capable of guiding complex financial innovations while maintaining ethical and legal coherence.